Pengaruh Keefektifan Pengendalian Internal Dan Kesesuaian Kompensasi Terhadap Kecenderungan Kecurangan Akuntansi Pada Perguruan Tinggi Negeri Di Kota Padang - Gina Septiana; Aris Prasetiyo (JURNAL PUNDI, 2021)
The tendency of bookkeeping extortion (TAF) is characterized by activities and arrangements that deliberately hide the actuality or do not provide original data on the grounds of deceiving or controlling. Surprisingly, in some cases, TAF was deliberately chosen because it was considered beneficial for itself, but more parties agreed not to give TAF a chance.This study aimed to examine the effect of the internal control effectiveness and suitability of rewardon the trend of accounting fraud at State Universities  in Padang. The sampling technique in this research used purposive sampling that the sample selection based on certain criteria corresponding author desired. The samples of this research are 90 employees accounting at each faculty in State Universities. Hypothesis testing results showthat the effectiveness of the internal control have negative effect on the tendency of accountingfraud and suitability of reward have negative effect towards the tendency of accounting fraud.